Bile Salt‐Derived Eu3+ Organogel and Hydrogel: Water‐Enhanced Luminescence of Eu3+ in a Gel Matrix. Issue 2 (9th January 2018) - Laishram, Raju; Maitra, Uday
Abstract: Eu 3+ was found to form gel with cholate in methanol and comparative study was done with the hydrogel. Water is a well known quencher of Eu 3+ luminescence, and its quenching rate constant is higher than that of MeOH. In a Eu 3+ derived luminescent material, therefore, the replacement of water by methanol should lead to enhanced Eu 3+ luminescence. However, significant pyrene‐mediated sensitizatized luminescence of Eu 3+ was observed in a Eu 3+ cholate hydrogel, but not in the methanolic gel . We provide experimental data that rationalize this apparent paradox. Abstract : EuCh was found to form gel in both methanol and water. Water is known to quenched Eu 3+ luminescence, but in the present system, we found that emission/sensitization of Eu 3+ was seen only in hydrogel and not in methanolic gel.